Detrusor underactivity in women: A current understanding. Issue 8 (20th August 2019) - Hartigan, Siobhan M.; Reynolds, W. Stuart; Dmochowski, Roger R.
Abstract: Aims: To examine the current understanding and management of detrusor underactivity (DUA) and underactive bladder (UAB) in women. Methods: A review of the current literature was performed with a specific focus on new management strategies and treatment options for women with DUA and UAB. Results: DUA has become an area of increased interest in recent years. Affecting up to 45% of older women undergoing urodynamic evaluation for non‐neurogenic lower urinary tract symptoms, DUA is common. There are a variety of possible etiologies including neurogenic or myogenic dysfunction. As there is currently no cure for DUA and no way to restore the ability of the detrusor muscle to contract, management of DUA in women is mostly focused on effective bladder drainage by urinary catheterization. Clean intermittent catheterization is the gold standard for bladder drainage however for a variety of reasons, women with DUA often are managed with indwelling urethral catheter or suprapubic tube. Medications, sacral neuromodulation, and the inFlow urinary prosthesis are also treatment alternatives or additions to catheterization. Novel therapies using stem cells and gene therapy are also under investigation for the treatment of DUA and UAB. Conclusions: DUA is likely more prevalent than recognized and undertreated in women. It is vital that further research in treatment options beyond catheterization be developed for these patients to offer patients a variety of treatment options.